Activity of aurisin A isolated from Neonothopanus nambi against methicillin-resistant Staphylococcus aureus strains - Getha Krishnasamy; Muhammad-Syamil Azahar; Shariffah-Nurhidayah S.A. Rahman; Vimalah Vallavan; Noraziah M. Zin; Mazlyzam A. Latif; Masahiro Hatsu (Elsevier, 2023)
Mycopharmaceuticals from basidiomycetes represent a promising source of new antimicrobials to overcome the challenges of multidrug-resistant bacteria. Here we report for the first time the in vitro activity of aurisin A, a dimeric sesquiterpenoid isolated from wild bioluminescent basidiomycetes Neonothopanus nambi DSM 24013, against methicillin-resistant Staphylococcus aureus (MRSA). Aurisin A revealed strong anti-MRSA activity with minimum inhibitory concentration 7.81 μg/mL against ATCC 33591 and ATCC 43300 reference strains, and BD 16876 and BD 15358 clinical strains. Activity against the clinical strains is 10- to 40-fold higher than that of the antibiotic fusidic acid. Furthermore, aurisin A proved to be more potent (MIC 3.91 μg/mL) in inhibiting growth of vancomycin-intermediate S. aureus (VISA) ATCC 700699 and displayed a rapid time-dependent bactericidal activity against MRSA (complete killing within 1 h). Additionally, aurisin A and oxacillin combination displayed synergy with notable decrease in the MICs of both compounds against MRSA. Notable synergism was also observed in combinations with linezolid and fusidic acid. Our findings indicate that aurisin A is a promising candidate for developing therapeutic agents against multidrug-resistant S. aureus and warrants further investigation.